Cutting for stone : a novel - Verghese, Abraham, 1955- (Vintage Books, 2010)
Twin brothers born from a secret love affair between an Indian nun and a British surgeon in Addis Ababa, Marion and Shiva Stone come of age in Ethiopia, where their love for the same woman drives them apart.